Analysis of Symbolism and Hidden Meaning in The Little Prince by Antoine de Saint-Exupery - Raihani, Shaheila; Sutrisno, Djoko (LPPM Universitas Pekalongan, 2025)
The Little Prince by Antoine de Saint-Exupéry is a children’s book that talks about the little prince, who comes from another planet that is also known as Asteroid B 612. One day, the little prince decided to leave his planet to learn about the meanings of life. Antoine de Saint-Exupéry wrote this book to show the young readers about the importance of love, friendships, the matter of consequence, and to express his experience on life. The research method that will be used in this research is the descriptive qualitative method and the approach with the theory of symbolism by Charles Baudeliare. In the result and discussion, the researcher will talk about the hidden meanings behind the story of The Little Prince. In this novel, the author represents several kinds of people in adulthood through the six characters that the little prince met in his adventure, they are the king, the conceited man, the businessman, the drinker, the lamplighter, and the geographer. The novel also explains the importance of friendship represented by the character of fox. In addition, the author also describes the relationship between him and his wife which is represented by the relationship between the little prince and his rose. Finally, the author expresses his trauma of grief through the melancholy relationship between the narrator and the little prince.